William Tyler, Meet Janet: How Two Extraordinary People Made Variable Stars Accessible To The Rest Of Us - Levy, David H. (İstanbul Kültür Üniversitesi Yayınları, 2005)
Bir ışık noktasının parlaklaşıp sönükleşmesini izleme fikri her zaman kolay iş değildir. Değişenleri yalnız bırakarak gezegen, kuyruklu yıldız ve derin uyaz gözlemciliğini benimsemiş çok iyi amatör astronomlar vardır. İyi bir şarap gibi değişen yıldız gözlemciliği de aquired bir tat olabilir. Neyse ki, bazı insanlar yıllar boyunca, bu alanı daha geniş bir yıldız aşığı kitlesine ulaştırmaya kariyerlerini ve hayatlarını adamışlardır. Bu sunum böyle iki kahramanın çalışmalarını kutlamaktadır; William Tyler Olcott ve Janet Mattei; değişen yıldız gözlemciliğini kendi nesillerinin kalplerine dokunan bir alana dönüştüren iki akıl hocası. Her ikisi de insanlara ulaşan gizemli bir yolla değişenler için bilgi ve hevesi birleştirmiştir. Bu çok özel astronomların çabaları olmasaydı, değişen yıldızlar bugün olduğu alan olamazdı.

The idea of watching a point of light bringhten and fade over a specific period of time is not always an “easy sell “—there are some very good amateur astronomers who have embraced the planets, comets, and deep sky observing while leaving variables alone. Like fine wines, variable star observing can be an aquired taste. Fortunately, over the decades, some people have dedicated their careers and lives to making the field accessible to the larger community of lovers of the stars. This presentation celebrates the work of two of these championbs—William Tyler Olcott and Janet Mattei, two mentors who transformed variable star observing into a field that touches the hearts of their generations. They both combined knowledge and enthusiasm for variables with an uncanny way of reaching out to people. Veriable stars would not be the field it is today were it not fort he efforts of these very special astronomers.
Keywords: yıldızlar; değişken yıldızlar; amatör astronom; William Yyler; Janet Mattei; stars; variable stars; amateur astronomers